A Retrospective analysis of the factors influencing Outcomes in Critically ill Obstetric Patients admitted in ICU - Dr. Shyam Kishore Panjiyar, Dr. Saurabh Bhandge* (Innovative Journal of Medical and Health Sciences, 2020)
Introduction: An indicator of pronounced maternal morbidity is intensive care unit (ICU) admissions of obstetric patients. Few studies have been published concerning ICU admissions of obstetric patients in the developing world, Based on the fact that the risk factors defining pronounced maternal morbidity and maternal mortality in the developing world are not fully established, the present retrospective study was conducted to analysed & evaluate the obstetric admissions to the ICU in an attempt to identify the risk factors influencing maternal outcome. Methods:This Retrospective Analytical study involved 100 randomly selected Obstetrical patients admitted to ICUs . Prior Consent was obtained from Local Randomly selected Tertiary care hospitals to see the records of the patients from MRD . The medical records for these patients were reviewed for the collection and classification of data including the patient characteristics, the obstetric history, the preexisting medical disorders and the causes that necessitated admission to the ICU. Results: Major obstetric and medical conditions requiring ICU admission were Haemorrhage , Hypertensive Disorders of Pregnancy (Preeclampsia , Eclampsia , PIH )Severe Anemia & Sepsis. The number of maternal deaths was 13 % of obstetric patients admitted in ICU in our study . The commonest causes of maternal mortality were hemorrhagic shock and multiorgan dysfunction syndrome. The observed mean SAPS II scores between the surviving group of patients and the nonsurviving group of patients was statistically significant. Conclusion: There is a need for HDU in tertiary care hospitals. Obstetric hemorrhage and hypertensive disorders of pregnancy are the major risk factors for ICU admission. Majority of complications occurred in women with gestational age of 37–42 weeks. There is a need to train obstetricians in obstetric medicine and critical care to do justice to these critically ill pregnant women. Focus of care for the obstetric patients who bear the major risk factors and who are admitted to the ICU should be carried out under the guidance of the ICU scoring systems such as the SAPS II & others like APACHE-II, SOFA scores. Key words: Retrospective analysis–Intensive care–Obstetrical care–SAPS II